Donation after circulatory death and its expansion in Spain. Issue 1 (February 2018) - Miñambres, Eduardo; Rubio, Juan J.; Coll, Elisabeth; Domínguez-Gil, Beatriz
Abstract : Purpose of review: Donation after circulatory death (DCD) is still performed in a limited number of countries. This article summarizes the development of DCD in Spain and presents recent Spanish contributions to gain knowledge on the potential benefits and the practical use of normothermic regional perfusion (nRP). Recent findings: DCD now contributes to 24% of deceased donors in Spain. The development of DCD has been based on an assessment of practices in the treatment of cardiac arrest and end-of-life care to accommodate the option of DCD; the creation of an adequate regulatory framework; and institutional support, professional training and public education. Appropriate posttransplant outcomes have been obtained with organs from both uncontrolled and controlled DCD donors. nRP is increasingly used, with preliminary data supporting improved results compared with other in-situ preservation/recovery approaches. Mobile teams with portable extracorporeal membrane oxygenation devices are making nRP possible in hospitals without these resources. To avoid the possibility of reestablishing brain circulation after the determination of death, a specific methodology has been validated. Summary: DCD has been successfully developed in Spain following a streamlined process. nRP may become a standard in DCD, although further evidence on the benefits of this technology is eagerly awaited.